Clinical evaluation of the ADE scorecards as a decision support tool for adverse drug event analysis and medication safety management. (6th September 2013) - Hackl, Werner O.; Ammenwerth, Elske; Marcilly, Romaric; Chazard, Emmanuel; Luyckx, Michel; Leurs, Pascale; Beuscart, Regis
Abstract : Aims: The prevention of adverse drug events (ADEs) demands co‐ordination of different health care professionals. ADE scorecards are a novel approach to raise the team awareness regarding ADE risks and causes. It makes information on numbers and on possible causes of possible ADE cases available to the clinical team. The aim of the study was to investigate the usage and acceptance of ADE scorecards by healthcare professionals and their impact on rates of possible ADEs. Methods: ADE scorecards were introduced in three departments of a French hospital. A controlled time series analysis of ADE data was conducted to assess the impact of the ADE scorecards. In addition, qualitative interviews and a standardized survey with all participating staff members were performed. Results: Physicians, nurses and pharmacists found ADE scorecards effective to increase medication safety and recommended future usage. The time‐series analysis did not show changes in rates of possible ADEs. Conclusion: ADE scorecards appear to be useful to raise awareness of ADE‐related issues among professionals. Although the evaluation did not show significant reductions of ADE rates, the participating physicians, nurses and pharmacists believed that the ADE scorecards could contribute to increased patient safety and to a reduction in ADE rates. Strategies need to be designed to integrate ADE scorecards better into the clinical routine and to increase the precision of ADE detection.